Water sorption isotherms of skimmed milk powder within the temperature range of 5–20 °C - Jitka Langová; Jiří Štencl; Václav Vlášek (Acta Universitatis Agriculturae et Silviculturae Mendelianae Brunensis, 2012)
Moisture sorption isotherms (MSI’s) of skimmed milk powder in the temperature range of 5–20 °C were determined using manometric method. MSI’s, which show the water content versus water activity (Aw) at a constant temperature, are used to describe relationships between water content and equilibrium state relative vapour pressure (RVP). The equilibrium moisture content (EMC) of skimmed milk powder samples is growing with an increase of Aw at a constant temperature both for water adsorption and desorption. Isotherms were found to be type II of Brunauer-Emmett-Teller classification. It is the type most common for foods. The shape of created isotherms was sigmoid. Structural modifications of crystals were observed during adsorption in the microscope, too. Critical value of EMC of tested samples corresponding to the Aw equal to 0.6 for adsorption was 6.50% MC (w.b.) at temperature 5 °C, 9.15% MC (w.b.) at temperature 10 °C, and 7.71% MC (w.b.) at temperature 20 °C. These values determine optimal conditions for storage from the point of view microorganisms grow, Aw<0.6.